Striatal Dopamine D2-Muscarinic Acetylcholine M1 Receptor–Receptor Interaction in a Model of Movement Disorders - Crans, René A. J.; Wouters, Elise; Valle-León, Marta; Taura, Jaume; Massari, Caio M.; Fernández-Dueñas, Víctor; Stove, Christophe P.; Ciruela, Francisco (Frontiers in Pharmacology, 2020)
Parkinson’s disease (PD) is a neurodegenerative disorder characterized by motor control deficits, which is associated with the loss of striatal dopaminergic neurons from the substantia nigra. In parallel to dopaminergic denervation, there is an increase of acetylcholine within the striatum, resulting in a striatal dopaminergic-cholinergic neurotransmission imbalance. Currently, available PD pharmacotherapy (e.g. pro-dopaminergic drugs) does not reinstate the altered dopaminergic-cholinergic balance. In addition, it can eventually elicit cholinergic-related adverse effects. Here, we investigated the interplay between dopaminergic and cholinergic systems by assessing the physical and functional interaction of dopamine D2 and muscarinic acetylcholine M1 receptors (D2R and M1R, respectively), both expressed at striatopallidal medium spiny neurons. First, we provided evidence for the existence of D2R-M1R complexes via biochemical (i.e. co-immunoprecipitation) and biophysical (i.e. BRET1 and NanoBiT®) assays, performed in transiently transfected HEK293T cells. Subsequently, a D2R-M1R co-distribution in the mouse striatum was observed through double immunofluorescence staining and AlphaLISA® immunoassay. Finally, we evaluated the functional interplay between both receptors via behavioral studies, by implementing the classical acute reserpine pharmacological animal model of experimental parkinsonism. Reserpinized mice were administered with a D2R-selective agonist (sumanirole) and/or an M1R-selective antagonist (VU0255035) and alterations in PD-related behavioral tasks (i.e. locomotor activity) were evaluated. Importantly, VU0255035 (10 mg/kg) potentiated the antiparkinsonian-like effects (i.e. increased locomotor activity and decreased catalepsy) of an ineffective sumanirole dose (3 mg/kg). Altogether, our data suggest the existence of putative striatal D2R/M1R heteromers, which might be a relevant target to manage PD motor impairments with less adverse effects.